Penguatan Mahasiswa Unzah Genggong dalam Memahami Pandangan Masa Vital dan Perkembangan Penghayatan pada Bayi - Antoni Antoni; Faisal Akbar; Endah Tri Wisudaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to strengthen the understanding of UNZAH Genggong students regarding the concept of the vital period and the development of awareness in infants. A qualitative approach was employed through interview and observation techniques to explore the process of improving this understanding. The findings indicate that structured learning and hands-on practice significantly enhance students’ knowledge of the vital period concept and the importance of awareness in supporting optimal infant development. Furthermore, the intervention emphasizes the need for integrating theory and practice in the learning process to improve students’ competencies in childcare and child development. The strategies implemented not only reinforce students’ conceptual understanding but also develop their practical skills, which are crucial in the context of early childhood education. The data show that educational strategies combining theory and practice can be sustained, providing a positive impact on the improvement of students’ competencies and the overall quality of early childhood education. Therefore, strengthening students’ understanding of the concepts of the vital period and infant awareness can make a significant contribution to better childcare quality and child development.